Ovarian Hemangioma: a rare case in a young girl - Patvekar, Meenal M.; Kolate, Dipak S.; Bhatnagar, Aditi B.; Gore, Charusheela R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
The ovary has a rich vascular supply. But the vascular tumors of the ovary are extremely rare. Ovarian masses are mostly discovered accidentally during surgery or imaging. These tumors may rarely be associated with systemic manifestations. Here we report a case of 17 year old young unmarried obese girl who presented with acute pain in abdomen and was treated laproscopically with conservation of ovaries. Histopathology report was suggestive of ovarian haemangioma. The diagnostic challenge and therapeutic rarity of such a tumour in a young unmarried girl has proven to be an exceptional case and an excellent investigative opportunity.